Impact assessment modeling of climatic conditions on spatial-temporal changes in surface biophysical properties driven by urban physical expansion using satellite images. (May 2022) - Shorabeh, Saman Nadizadeh; Kakroodi, A.A.; Firozjaei, Mohammad Karimi; Minaei, Foad; Homaee, Mehdi
Highlights: The climatic condition's effect on surface properties changes are driven by urban growth was assessed. Urban growth patterns of metropolises were different based on their geographical, environmental, and natural conditions. The vegetation and LST conditions of metropolises were varied based on their climate. The biophysical properties difference of inner and outer city areas with wet climates was greater than arid climates. Changes in surface biophysical properties with humid climates were greater than the arid climate. Abstract: This study was aimed to explore the effect of climatic conditions on changes in surface biophysical properties driven by urban growth using remote sensing and climatic data. For this purpose, Landsat 5 and 8 multi-time satellite images of Tabriz, Rasht, Yazd and Mashhad metropolises have been used. Firstly, a land use/cover map was prepared for the study area using the support vector machine (SVM) algorithm. In the secondly, surface biophysical properties including land surface temperature (LST) data, and brightness, greenness, and wetness properties were extracted using single channel algorithm and tasseled-cap band transformation, respectively. Then, their spatial and temporal variations across the study area were investigated. In the third step, the effect of climatic conditions on the spatial-temporal Changes in surface biophysical properties driven by urban physical expansion were investigated. The results showed the area of built-up area in Mashhad, Rasht, Tabriz, and Yazd has increased by 97, 148, 106 and 145 % from 1990 to 2019. The difference in surface biophysical properties inside and outside the cities was higher in cities with wet climates (e.g. Rasht) than cities with dry and hot climates (e.g. Yazd). The effect of urban physical expansion on temporal changes in surface biophysical properties was more pronounced in metropolises with humid climates than those in arid climates. According to our findings, long-term spatial and temporal analysis can help decision-makers to better plan for the reduction and control of LST changes according to the dominant climatic conditions of different metropolises.